Обгрунтування крайових умов оптимального режиму реверсування роликової формувальної установки за прискоренням третього порядку - Ловейкін, В. С.; Почка, К. І. (Техніка будівництва, 2020)
For the purpose of increase of reliability and durability of roller forming installation the combined mode of back and forth motion of the forming cart with a reversal under optimum regional conditions on acceleration of the third order is calculated. The design of the drive of installation in a type of the cam mechanism is developed and the cam profile for providing the combined mode of back and forth motion of the forming cart is constructed. The design of roller forming installation with the drive from the high-moment step engine which is built in the rolling rollers of the forming cart of installation is also offered.